Oxali(IV)Fluors: fluorescence responsive oxaliplatin(IV) complexes identify a hypoxia-dependent reduction in cancer cells - Boulet, M; Bolland, H; Hammond, E; Sedgwick, A (American Chemical Society, 2023)
Platinum(IV) anticancer agents have demonstrated the potential to overcome the limitations associated with the widely used Pt(II) chemotherapeutics, cisplatin, carboplatin, and oxaliplatin. In order to identify therapeutic scenarios where this type of chemotherapy can be applied, an improved understanding on the intracellular reduction of Pt(IV) complexes is needed. Here, we report the synthesis of two fluorescence responsive oxaliplatin(IV)(OxPt) complexes, OxaliRes and OxaliNap. Sodium ascorbate (NaAsc) was shown to reduce each OxPt(IV) complex resulting in increases in their respective fluorescence emission intensities at 585 and 545 nm. The incubation of each OxPt(IV) complex with a colorectal cancer cell line resulted in minimal changes to the respective fluorescence emission intensities. In contrast, the treatment of these cells with NaAsc showed a dose-dependent increase in fluorescence emission intensity. With this knowledge in hand, we tested the reducing potential of tumor hypoxia, where an oxygen-dependent bioreduction was observed for each OxPt(IV) complex with <0.1% O2 providing the greatest fluorescence signal. Clonogenic cell survival assays correlated with these observations demonstrating significant differences in toxicity between hypoxia (<0.1% O2) and normoxia (21% O2). To the best of our knowledge, this is the first report showing carbamate-functionalized OxPt(IV) complexes as potential hypoxia-activated prodrugs.